Topographic processing in developmental prosopagnosia: Preserved perception but impaired memory of scenes. Issue 7 (16th November 2016) - Klargaard, Solja K.; Starrfelt, Randi; Petersen, Anders; Gerlach, Christian
ABSTRACT: Anecdotal evidence suggests a relation between impaired spatial (navigational) processing and developmental prosopagnosia. To address this formally, we tested two aspects of topographic processing – that is, perception and memory of mountain landscapes shown from different viewpoints. Participants included nine individuals with developmental prosopagnosia and 18 matched controls. The group with developmental prosopagnosia had no difficulty with topographic perception, but was reliably poorer in the retention of topographic information. Additional testing revealed that this did not reflect a general deficit in visual processing or visual short-term memory. Interestingly, a classical dissociation could be demonstrated between impaired face memory and preserved topographic memory in two developmental prosopagnosics. We conclude that impairments in topographic memory tend to co-occur with developmental prosopagnosia, although the underlying functions are likely to be independent.